2021
DOI: 10.1007/s13555-021-00631-8
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Experience of Biologic Therapy in Atopic Dermatitis: A Qualitative Focus Group Study of Physicians and Patients in Europe and Canada

Abstract: Introduction The Biologics in Atopic Dermatitis: Experiences & Learnings (BADEL) project aims to improve real-life understanding of how, where, and when biologics can play a role in the treatment of atopic dermatitis (AD) from the perspective of healthcare professionals (HCPs) and patients. Methods Individual experiences of 24 patients with moderate-to-severe AD and who had been treated with biologic therapy (dupilumab) for ≥ 3–6 months, and 20 HCPs with a sub-specialty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Fourteen studies addressed concern about adverse effects of treatment. 14,24,25,30,31,37,42,44,46,47,50,60,71,72 Patients and their caregivers consider the trade-off between the benefits and harms of treatments for AD (moderate certainty): "It really all boils down to side effects…As long as it's helping him, I want him to take it. But it all depends on what the side effects are."…”
Section: Fear and Concern About Adverse Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourteen studies addressed concern about adverse effects of treatment. 14,24,25,30,31,37,42,44,46,47,50,60,71,72 Patients and their caregivers consider the trade-off between the benefits and harms of treatments for AD (moderate certainty): "It really all boils down to side effects…As long as it's helping him, I want him to take it. But it all depends on what the side effects are."…”
Section: Fear and Concern About Adverse Effectsmentioning
confidence: 99%
“…Eleven studies reported patients preferring to use topical corticosteroids for as short as possible (low certainty evidence). 14,15,20,24,31,34,46,60,65,70,71 Participants preferred starting topical corticosteroids when AD is poorly controlled, and discontinuing topical corticosteroids when eczematous lesions resolved. This results in a treatment strategy where patients and caregivers use topical corticosteroids for the minimum time necessary to control flares: "Steroid creams…[make] your illness worse if they're used incorrectly.…”
Section: Preference To Use Topical Corticosteroids For the Minimum Am...mentioning
confidence: 99%
See 3 more Smart Citations